A Genealogy of Dissent : Southern Baptist Protest in the Twentieth Century - Stricklin, David, 1952- (Book collections on Project MUSE., 2015)
Between the Civil War and the turn of the last century, Southern Baptists gained prominence in the religious life of the South. As their power increased, they became defenders of the racial, political, social, and economic status quo. By the beginning of this century, however, a feisty tradition of dissent began to appear in Southern Baptist life as criticism of the center increased from both the left and the right. The popular belief in a doctrine of ""once saved, always saved"" led progressive Baptists to claim that moderates, once saved, did not address the serious social and political prob.